Amplitude Noise of Electrical Oscillators Based on the LTV Model - Hashemi, S. A.; Ghafoorifard, H.; Abdipour, A. (Elektronika ir Elektrotechnika, 2012)
In this paper, using the Linear Time Variant (LTV) noise model of oscillators, an analytical expression for Amplitude Impulse Sensitivity Function (A-ISF) based on the limit cycle of the oscillator is derived for the first time. Also Considering the existing expression for Phase Impulse Sensitivity Function (P-ISF), it is shown that P-ISF and A-ISF are correlated. The derived A-ISF is used to simulate the amplitude noise of the oscillators in the 1/f2 region of the noise spectrum by the LTV model. Simulation and experimental results show the validity of the derived formula. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2607